Experimental demonstration of novel imaging geometries for x‐ray fluorescence computed tomography. Issue 6 (8th May 2013) - Fu, Geng; Meng, Ling‐Jian; Eng, Peter; Newville, Matt; Vargas, Phillip; Riviere, Patrick La
Abstract : Purpose: X‐ray fluorescence computed tomography (XFCT) is an emerging imaging modality that maps the three‐dimensional distribution of elements, generally metals, in ex vivo specimens and potentially in living animals and humans. At present, it is generally performed at synchrotrons, taking advantage of the high flux of monochromatic x rays, but recent work has demonstrated the feasibility of using laboratory‐based x‐ray tube sources. In this paper, the authors report the development and experimental implementation of two novel imaging geometries for mapping of trace metals in biological samples with ∼50–500 μ m spatial resolution. Methods: One of the new imaging approaches involves illuminating and scanning a single slice of the object and imaging each slice's x‐ray fluorescent emissions using a position‐sensitive detector and a pinhole collimator. The other involves illuminating a single line through the object and imaging the emissions using a position‐sensitive detector and a slit collimator. They have implemented both of these using synchrotron radiation at the Advanced Photon Source. Results: The authors show that it is possible to achieve 250 eV energy resolution using an electron multiplying CCD operating in a quasiphoton‐counting mode. Doing so allowed them to generate elemental images using both of the novel geometries for imaging of phantoms and, for the second geometry, an osmium‐stained zebrafish. Conclusions: The authors have demonstrated the feasibility of these two novel approaches to XFCT imaging. While they use synchrotron radiation in this demonstration, the geometries could readily be translated to laboratory systems based on tube sources.